2016
DOI: 10.1016/j.envpol.2016.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Pollution by metals and toxicity assessment using Caenorhabditis elegans in sediments from the Magdalena River, Colombia

Abstract: a b s t r a c tThe Magdalena River is the most important river in Colombia, supplying over 70% of the population of fish and drinking water, and it also is the main river transportation way of the country. It receives effluents from multiple sources along its course such as contaminant agricultural and industrial discharges. To evaluate the toxicity profile of Magdalena River sediments through endpoints such as survival, locomotion, and growth, wild type strains of Caenorhabditis elegans were exposed to aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 79 publications
0
33
0
5
Order By: Relevance
“…Studies have shown that these industries contribute to increased concentration of heavy metals in river sediment. For instance, the heavy metal pollution derived from the Magdalena River in Columbia was a clear consequence of direct discharges from coal mining and oil transportation sources (Tejeda-Benitez et al 2016). Kumarkhali textile in Kushtia industrial area of Bangladesh contaminated Goral River sediment with toxic heavy metals (Islam et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that these industries contribute to increased concentration of heavy metals in river sediment. For instance, the heavy metal pollution derived from the Magdalena River in Columbia was a clear consequence of direct discharges from coal mining and oil transportation sources (Tejeda-Benitez et al 2016). Kumarkhali textile in Kushtia industrial area of Bangladesh contaminated Goral River sediment with toxic heavy metals (Islam et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Tejeda-Benitez et al [32], 99% of the population of Colombia, including Bogota, are located in the Magdalena watershed, which is exposed to land-use practices such as illicit crops, deforestation, agriculture, industry, mining and increasing rates of urbanization. Furthermore, clear evidence of high loads of heavy metals in the majority of Colombian rivers has been reported, with the Bogota River being one of the most polluted by these kind of contaminants [33].…”
Section: Discussionmentioning
confidence: 99%
“…Locomotion: Nematodes in L2 larval stage were exposed for 24 h to AgNPs concentrations. Then they were scored for the number of body bends in 20 s. A body bend was assumed as a change in the direction of the posterior bulb of the pharynx along the axis [15]. Growth: L2 larval stage were exposed to AgNPs (500, 1000, 2000 and 4000 g/L) for 72 h, with addition of Escherichia coli OP50 each 24 h, each experiment was done by triplicate.…”
Section: 3toxicological Assaymentioning
confidence: 99%
“…Growth: L2 larval stage were exposed to AgNPs (500, 1000, 2000 and 4000 g/L) for 72 h, with addition of Escherichia coli OP50 each 24 h, each experiment was done by triplicate. The body length after exposure was measured using images from a Nikon smz 745T microscope and the ImageJ software [15]. Mortality: C. elegans in L4 larval stage were exposed for 24 h to AgNPs (500, 1000, 2000 and 4000 g/L).…”
Section: 3toxicological Assaymentioning
confidence: 99%
See 1 more Smart Citation